Transmission Channels and Impacts of Energy Use on Health Outcomes in Asia - Zhang, Xiaoyan; Chen, Minjuan; Li, Jinbao (Frontiers in Public Health, 2022)
Today, the developing economies continue to tackle the penalties of the energy use and its influence on their environmental and socio-economic prosperity, and the developed economies are concentrating on promoting programs and policies to improve and sustain the endowment of adequate energy consumption that pledges less carbon emissions and threats to human health. Currently, millions of people face a dearth of access to reliable, affordable, and clean energy to fulfill their daily requirements. Thus, the mounting need for energy use portends hazardous consequences on human health. This paper investigates the transmission channels and impact of energy consumption on health outcomes in Asia by adopting a panel of selected Asian economies for the period from 1991 and 2019. The findings of the study show that energy causes a rise in infant mortality rate and a reduction in life expectancy. Furthermore, the study found that a high degree of pollution emissions causes a rise in infant mortality and a decline in life expectancy.